Neurodegenerative diseases as proteinopathies-driven immune disorders - Fausta Ciccocioppo (Neural Regeneration Research, 2020)
In the pathophysiology of neurodegenerative disorders, the role of misfolded protein deposition leading to neurodegeneration has been primarily discussed. In the last decade, however, it has been proposed a parallel involvement of innate immune activation, chronic inflammation and adaptive immunity in the neurodegeneration mechanisms triggered by proteinopathies. New insights in the neurodegenerative field strongly suggest a role for the immune system in the pathophysiology of neurodegenerative disorders. Therefore, the hypothesis underlining the modulation of the innate and the adaptive immune system in the events linked to brain deposition of misfolded proteins could open new perspectives in the setting of specific immunotherapeutic strategies for the treatment of neurodegenerative diseases. Therefore, we have reviewed the pathogenic hypothesis in neurodegenerative pathologies, underling the links between the deposition of misfolded protein mechanisms and the immune activation.